The Regional Research And Development Centre of the Asean Institute of Technology, Bangkok - anonymous anonymous (ASEAN Journal on Science and Technology for Development, 1986)
The Asian Institure of Technology (AJT) is an autonomouse, International postgraduate Institute. It provides advanced education in engenering, science and allied fields through academic programme loading to Master's and Doctoral degree and Diplomat, and through research programmes are related  closely to the needs of Asia.